Decreased Stroke Presentation Rates at a Comprehensive Stroke Center during COVID-19. (3rd January 2021) - Dowlatshahi, Dar; Stotts, Grant; Bourgoin, Aline; Gocan, Sophia; Dunn, Laura; Powell, Jodi; Silver, Frank L.; Walker, Greg; Yogendrakumar, Vignan; Fahed, Robert; Blacquiere, Dylan; Shamy, Michel
ABSTRACT: We reviewed stroke care delivery during the COVID-19 pandemic at our stroke center and provincial telestroke system. We counted referrals to our prevention clinic, code strokes, thrombolysis, endovascular thrombectomies, and activations of a provincial telestroke system from February to April of 2017–2020. In April 2020, there was 28% reduction in prevention clinic referrals, 32% reduction in code strokes, and 26% reduction in telestroke activations compared to prior years. Thrombolysis and endovascular thrombectomy rates remained constant. Fewer patients received stroke services across the spectrum from prevention, acute care to telestroke care in Ontario, Canada, during the COVID-19 pandemic.